From Leadership to Innovation: Managing Employee Creativity - Masduki Asbari; John Tampil Purba; Evo Sampetua Hariandja; Niko Sudibjo (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study focuses on innovation by individual employees. This study aimed to measure the effect of leadership autonomy support (LAS) on individual innovative behavior (IIB) of MSMEs' employees in Banten which are mediated by individual creativity (IC). The data collection was done by simple random sampling of the employees of five MSMEs in Banten. The returned and valid questionnaire results were 97 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that leadership autonomy support has a positive and significant effect on individual innovative behavior, both directly and indirectly through mediating individual creativity. This new research proposed a model for building individual innovative behavior among the MSMEs' employees in Banten through enhancing leadership autonomy support with individual creativity as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.